MAPPING EARTHQUAKE HAZARD BY USING GIS AND MULTI-CRITERIA ANALYSIS IN BANTUL REGENCY - Nugroho, Budi Haryo; Hardjomidjojo, Hartrisari; Subagio, Habib (GEOMATIKA, 2010)
Earthquakes are natural events that are difficult to predict and are always causing casualties or major damage. The concept of mitigation associated with the earthquake hazard requires a hazard map that can be used as the basis of land use regulation in order to avoid casualties in case of disaster. Map of the earthquake hazard have been prepared based on a combination of geologic map information; lithology (rock structure) map, earthquake intensity map, slope map, and a map of fault lines. GIS Method of multi-criteria analysis is used as a means of model simulation. The result of the disaster analysis map shows 13% of the area categorized as low or very prone to stability in case of earthquakes, with the main factor is the existence of fault lines. The result of comparison with previous studies showing there is a similarity level of damage and disaster map analysis, with notes need to increase the level of detail map geological information to improve the accuracy of maps of disaster.Keywords: earthquake, hazard, GIS, multi-criteria analysisABSTRAKGempa adalah kejadian alam yang sulit diprediksi dan selalu menimbulkan korban jiwa maupun kerusakan yang besar. Konsep mitigasi terkait dengan bencana gempa bumi memerlukan sebuah peta bahaya yang bisa dijadikan dasar pengaturan penggunaan lahan dengan tujuan menghindari korban jika terjadi bencana. Peta bencana gempa bumi disusun berdasarkan kombinasi peta informasi geologi yaitu peta litologi (struktur batuan), peta intensitas gempa, peta kelerengan, dan peta jalur patahan. Metode GIS multi-kriteria analisis digunakan sebagai alat simulasi model . Hasil peta analisis bencana menunjukan 13% area masuk kategori stabilitas rendah atau sangat rawan jika terjadi gempa bumi, dengan faktor utama yaitu keberadaan jalur patahan. Hasil komparasi dengan studi-studi sebelumnya menunjukan ada kesamaan tingkat kerusakan dan peta bencana hasil analisis, dengan catatan perlu adanya peningkatan tingkat kedetailan peta informasi geologi untuk meningkatkan akurasi peta bencana.Kata kunci: gempa bumi, rawan, SIG, analisa multi kriteria